2014
DOI: 10.1115/1.4026229
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Vertebral Artery Stenosis Treated With Different Stents

Abstract: We sought to investigate the effects of endovascular stents with different links for treating stenotic vertebral artery and to determine the relationship between the shape of the link and in-stent restenosis (ISR). We also attempted to provide scientific guidelines for stent design and selection for clinical procedures. Models of three types of stent with different links (L-stent, V-stent, and S-stent) and an idealized stenotic vertebral artery were established. The deployment procedure for the stent in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The material properties of these models were extracted from the literature, and the stent was made of 304 stainless steel [Qiao et al (2014)]. According to Pericevic et al's research [Pericevic et al (2009)], the plaque without calcification or with a low level of calcification was unstable, while the stiffer calcified plaque could reduce the level of stress within the arterial tissue for a given inflation pressure.…”
Section: Meshed Models and Materials Propertymentioning
confidence: 99%
“…The material properties of these models were extracted from the literature, and the stent was made of 304 stainless steel [Qiao et al (2014)]. According to Pericevic et al's research [Pericevic et al (2009)], the plaque without calcification or with a low level of calcification was unstable, while the stiffer calcified plaque could reduce the level of stress within the arterial tissue for a given inflation pressure.…”
Section: Meshed Models and Materials Propertymentioning
confidence: 99%
“…The stented vessel has a compliance mismatch with the normal vessels at the two ends of stent. For this reason, stenting causes a significant straightening of vessel, and part of the blood can be folded or bounced back which causes disturbed blood flow [13][14][15][16][17][18]. Wu et al performed numerical simulation of solid mechanics of the influence of stent on vessel, but they believed that blood flow mechanics had greater impact on ISR than the local solid mechanics of stent [14].…”
Section: Hemodynamic Study On Stented Arterymentioning
confidence: 99%
“…Qiao et al designed three types of stent with different links (L-stent, V-stent and S-stent) and an idealized stenotic vertebral artery [18]. The deployment procedure for the stent in the stenotic vertebral artery was simulated for solid mechanics analysis.…”
Section: Hemodynamic Study On Stented Arterymentioning
confidence: 99%
“…Over expansion, large strut gap and highly compliant balloon materials creates more contact area and contact stresses on artery and the stent over sizing may lead to high intramural wall stress (Bukala et al, 2016). Another important design parameter is the strut connector and the effect of different shapes of strut connector ('U', 'V' and 'S') on in-stent restenosis was investigated by considering both solid and fluid structural analysis and observed that 'S' shaped connector has better flexibility and less stress and foreshortening (Qiao et al, 2014). The study by Imani et al (2013) was more realistic as they considered artery and plaque together with stent and balloon to analyze the probability of restenosis.…”
Section: Introductionmentioning
confidence: 99%